THE INFLUENCE OF CELEBRITY ENDORSEMENT AND BRAND IMAGE ON PANTENE SHAMPOO PURCHASE DECISIONS ON STUDENTS OF THE FACULTY OF MANAGEMENT ECONOMICS, KRISNADWIPAYANA UNIVERSITY - Hizbi Auliya Rahman; Ike Irawati; Iwan Kurniawan Subagja (Krisnadwipayana International Journal of Management Studies, 2024)
This study aims to determine the influence of Celebrity Endorsement and Brand Image on the Purchasing Decision of Pantene Shampoo among students of the Faculty of Economics and Management, Krisnadwipayana University, both partially and simultaneously. The research was conducted on Pantene shampoo consumers using a quantitative approach by collecting data and distributing questionnaires to 68 respondents. This study employed non-probability sampling with a purposive sampling technique. The data collected were analyzed using multiple linear regression analysis techniques. The research results show that: (1) Partially, Celebrity Endorsement has a positive and significant influence on Purchasing Decisions. (2) Partially, Brand Image has a positive and significant influence on Purchasing Decisions. (3) Simultaneously, Celebrity Endorsement and Brand Image have a positive and significant influence on Purchasing Decisions.